Tool-assisted model for software requirement negotiation - Lau, Hong Sheng (2015)
Requirement negotiation plays an important role in software engineering in order to get the requirements which are agreed by various stakeholders. Stakeholder with different background and culture tend to have different perceptions and perspectives. These differences will lead to conflicts, whether conflicts between stakeholders or conflicts between requirement, resources and capability. It is very difficult to solve conflict issue as each person see things in a different way. Here, Negotiation is vital to solve these conflicts and come to an agreement.Although requirement negotiation plays such a crucial role, the research of these field are still at the beginning of the stage as people tend to overlook or skip the process of requirement elicitation which involve requirement negotiation and immediately start with the development of system in order to save time. Due to advancement of technology nowadays, software system has become very important and widely use, one of the most popular software devices is smartphone where almost everyone already has one in their hand. And other technology also requires the presence of software in order to make the system intelligence, thus it is very important to gather the requirement of the system first before developing the system. As requirement negotiation is regards as one of the first step in any software system life cycle,one mistake in it will propagate to the other stages of software development life cycle, thus increase budget and time. Furthermore, different stakeholders may stay at different location.This research is about developing tool-assisted model for software requirement negotiation which provides a negotiation system for the stakeholders in order to reduce conflicts, ease the process of requirement elicitation and also allow distributed requirement elicitation in order to come to an agreement faster and thus obtain the requirements in a more convenient and efficient way.